A Lustful Passion for Clarification: Bildung, Aufklärung, and the Sight of Sexual Imagery - Stephanie D'Alessandro (Studies in 20th & 21st Century Literature, 1998)
The equation of education and self-cultivation was an Enlightenment ideal which has become a hallmark of bourgeois culture. Prizing Bildung, the bourgeoisie professed an appreciation for art, music, and literature. Within their libraries, comprehensive scholarly texts intended for academic and well-educated, lay audiences occupied a special place. Marrying illustration with academic investigation, the Sittengeschichte (history of morals) could also be found on the bourgeois library shelf and afforded its readers a glimpse into a world outside the strict parameters of bourgeois propriety. During the Weimar Republic, the demand for illustrated Sittengeschichten increased dramatically among the bourgeoisie, meeting their ideal of Bildung and intersecting with the more general eroticization of visual imagery at the time. Images were transformed into legitimate source material through the manner in which they were accessed and controlled by readers; potentially obscene material was domesticated in books by associations of class and culture. However, while they served an instructional need, the books also met an erotic market demand. In considering them, the social needs, sexual anxieties, and bodily desires of reading audiences commingle on these pages, revealing useful insights into the bourgeois institutions of culture and moral order in 1920s Germany.
Keywords: education; self-cultivation; Enlightenment; ideal; Enlightenment ideal; bourgeois culture; Bildung; art; music; literature; comprehensive scholarly texts; academic; well-educated; lay audience; Sittengeschichte; history of morals; propriety; Weimar Republic; illustrated; illustration; eroticization; visual imagery; source material; obscene material; domesticated; class; culture; erotic market; social needs; sexual anxieties; bodily desires; Germany; 1920s